Responses of bacterioplankton, particle- and colony-attached bacterial communities to Phaeocystis globosa blooms in Mirs Bay, China - Shi, Rongjun; Qi, Zhanhui; Han, Tingting; Dai, Ming; Zhang, Shufei; Huang, Honghui (Frontiers in Marine Science, 2023)
Microalgae blooms are a frequent occurrence in coastal waters worldwide. It is reasonable to assume that these blooms have various influences on bacterial communities, which in turn may affect the development and dissipation of the bloom. However, the bacterial community characteristics, particularly of attached bacteria, associated with microalgae blooms remain unclear. In this study, we investigated the community profiles of bacteria using high-throughput sequencing during a Phaeocystis globosa bloom in Mirs Bay, southern China, in January 2021. Bacteria living in three habitats, i.e., bacterioplankton, particle-attached bacteria, and colony-attached bacteria, were studied from the exponential growth phase to the decline growth phase of the bloom. Distinct variations in bacterial community composition existed among the three habitats. Bacteroidota, Proteobacteria, and Cyanobacteria were the dominant phyla of bacterioplankton, particle–attached bacteria, and colony-attached bacteria, respectively. Richness and diversity were significantly highest (p < 0.01) in particle-attached bacteria, followed by bacterioplankton, and lowest in colony-attached bacteria. The community diversities of bacterioplankton and particle-attached bacteria decreased significantly (p < 0.05) as the bloom shifted from the exponential to the decline phase. During the decline growth phase of the bloom, Bacteroidota and Verrucomicrobiota were the dominant remarkably abundant bacteria in the bacterioplankton community, whereas Verrucomicrobiota was dominant in the particle-attached bacteria community. No significant difference was observed in the colony-attached bacterial community between the exponential and decline phases of the P. globosa bloom owing to their complex network. The results of this study suggest that P. globose bloom has a profound impact on marine bacteria, particularly species that can decompose organic matter, which could play a crucial role in the dissipation of algal blooms.